PERSPEKTIF HUKUM ISLAM TERHADAP ADAT PANCER (STUDI KASUS DI DESA PESUCEN KECAMATAN KALIPURO KABUPATEN BANYUWANGI) - Samsul Arifin (Wasīlah: Journal Of Sharia Sciences, 2026)
Allah SWT has established rules for His servants regarding marriage in Islamic law. One of them is that it is permissible to marry a cousin. However, sometimes there is a clash between customary law and Islamic law and even becomes a difficult problem to solve, even often becoming a specter that is considered bid'ah dlalalah by some scholars, even though when viewed from the perspective of the history of Islam's success because it can make customs as a field of da'wah. In this study will examine customs if violated will have fatal consequences for a family even though in Islamic law if doing so is not a problem meaning Islam is not prohibited. This study is a qualitative study that describes the problems obtained from the results of interview findings to become a conclusion that has a basis. Not apart from that, the researcher also looks at previous studies as a legal basis. Al, results; The perspective of Islamic Law on the Pancer custom in Pesucen Village, Kalipuro District, Banyuwangi, categorizes the Pancer custom as a damaged custom (fasid) and cannot be used as a legal basis because it does not comply with the requirements contained in the custom. This Pancer custom has also violated the provisions of the Sharia by forbidding what is halal, and has even violated the arguments of Muttafaq `alaih.